CHARACTERISTICS OF SELF-DETERMINATION OF STUDENTS WITH DISABILITIES - Serdiuk, Liudmyla; Baranauskienė, Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article describes the psychological characteristics of students with disabilities. Their individual psychological characteristics are identified and they indicate the existence of effective models of interactions with their social environment, adequate self-acceptance, enough active life philosophy in such students. The article determines that such personality formations as life goals, personal autonomy, desire for personal growth, self-confidence are the most important for the development of self-determination of students with disabilities.